Steady State of Anaerobic Hybrid Bioreactor with Acidogenesis Phase for Biohydrogen Production from Palm Oil Mill Wastewater - Adrianto Ahmad; David Andrio; M Dalil; Amir Hamzah (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2026)
The utilization of industrial waste as an alternative energy source, such as Palm Oil Mill Effluent (POME), represents a promising approach, as it has a high potential to be converted into energy while simultaneously reducing environmental pollution. This research aims to achieve a steady state condition, so that it can be operated continuously using a pilot scale acidogenesis phase anaerobic hybrid bioreactor with a capacity of 12.5 L. This study employed a 12.5 L laboratory reactor operated at a controlled 24-hour Hydraulic Retention Time (HRT) to realistically represent the interactions and operating conditions commonly encountered in practical environmental systems. The results of the study showed that the seeding and acclimatization process lasted for 16 days and the start-up stage lasted for 71 days until the steady state of anaerobic hybrid bioreactor was achieved with pH conditions of 7. The Chemical Oxygen Demand (COD) loading rate was 2,240 mg/L-hour, COD concentration of 3,750 mg/L, alkalinity concentration of 1,920 mg/L, the Volatile Fatty Acids (VFA) concentration of 589 mg/L. The Total Solids (TS) concentration was 30,800mg/L and Total Suspended Solids (TSS) concentration of 9,400mg/L. The Total Volatile Solids (TVS) concentration was 24,100mg/L, the Volatile Suspended Solids (VSS) concentration of 3,100mg/L and biogas production of 1.8 L/hour. The steady state of the acidogenesis phase anaerobic hybrid bioreactor with a hydraulic retention time of 1 day can obtain a COD removal efficiency of 93.3% with a VFA/Alkalinity ratio of 0.3.